How News Organizations Sell Native Advertising: Discourses of Integration and Separation on In-House Content Studio Web Sites. (11th June 2022) - Carlson, Matt; Locke, Andrew
ABSTRACT: This study adds to the growing literature on native advertising and journalism by analyzing how seventeen prominent news organizations promote their in-house content studios on their web sites. As public-facing spaces oriented toward attracting clients, these sites are understood as discursive artifacts that provide insight into how news organizations negotiate their allegiance to norms of journalistic autonomy while simultaneously developing the role of creating paid advertising campaigns that sit alongside news content. Our analysis reveals that news organizations simultaneously engage in discourses of integration and separation between native advertising and news content. They signal the integration between news and advertising through the usage of "story" as an umbrella term for digital content while also maintaining separation through nuanced language choices that imply some degree of distance between news and native advertising. These diverging discourses demonstrate how fraught native advertising is for news organizations striving to be recognized as legitimate providers of authoritative news while attempting to bolster revenues in face of the difficulties arising with the digital advertising market. These findings draw on and expand discursive theories in journalism studies by broadening inquiry beyond news content to encompass the complex terrain of content production emerging within the digital space.